Cervical Cancer Control in Antioquia and Medellín 1980-2010 - Marleny Valencia Arredondo (Universidad Nacional de Colombia, 2014)
Objective: Rebuild from the actors, the programs implemented in Antioquia and Medellin from 1980 to 2010. Materials and methods: qualitative study of control programs for cervical cancer in Antioquia and Medellin from the actors, taking into account the influence of healthcare system reforms and the different administrations. The information was obtained by documenting and depth interviews with 15 stakeholders related to control activities of this neoplasm review. Results: In the department and the municipality have worked two programs, being more structured program of detection and control of cervical cancer those that ran from 1990 to 199. After the "Ley 100" there have only been disjointed activities and with little impact on mortality from this neoplasm. Conclusions: The developed programs have had direct inuence of changes of administrations, healthcare system and regulation reforms, to which the responsibilities of the different activities have accordingly uctuated, what shows the importance of the political will to take forward such programs. As today, and for over a decade, both Colombia and Antioquia lack of properly structured cervical cancer control programs.